Coal-Based Economy Kuznet Kurve's Environmental Approach in East Kalimantan Province - Priyagus (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
The focus of this study is to investigate the relationship between economic growth and carbon emissions proxied by coal in East Kalimantan province for the 2009-2021 data period. The analysis model uses standard EKC with the Robust Least Square method. The results of the analysis explain that the standard EKC is not obtained significantly. The two variables do not have causality and long-term relationships (cointegration). East Kalimantan's economic growth tends to increase emissions or is not yet environmentally. Changes in the coal-based economic structure are carried out gradually and sensitivity and involvement of all parties are needed to reduce carbon emissions